2023
DOI: 10.3390/biomedicines11020252
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Expression of GATA4 and GATA6 with the Clinical Characteristics and Prognosis of Resectable Pancreatic Adenocarcinoma

Abstract: GATA4 and GATA6 are transcription factors involved in the differentiation and development of PDAC. GATA6 expression is related to the classic molecular subtype, while its absence is related to the basal-like molecular subtype. The aim was to determine the clinical utility of IHC determination of GATA4 and GATA6 in a series of patients with resected PDAC. GATA4 and GATA6 expression was studied by IHC in TMA samples of normal tissue, PanIN, tumor tissue and lymph node metastases from a series of 89 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For pragmatic subtyping in tissue sections, GATA6 protein is the only routinely used staining‐based biomarker, including in clinical trial settings [12]. We observed differences in expression of GATA6 , not only within patients but even up to the level of single pancreatic tumour ducts.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…For pragmatic subtyping in tissue sections, GATA6 protein is the only routinely used staining‐based biomarker, including in clinical trial settings [12]. We observed differences in expression of GATA6 , not only within patients but even up to the level of single pancreatic tumour ducts.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to that valuable study, we integrated a systematic and quantitative approach with markers directly informed by the transcriptomic signatures from two of the seminal publications of PDAC transcriptomic subtypes [4,5]. Indeed, while GATA6 as a marker of the classical subtype has been well validated [11,12,31], many studies nowadays use protein markers presumed to reveal the basal-like subtype. We showed that a marker such as deltaNp63/P40 labels only a fraction of basal-like tumour cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although retrospective studies have previously highlighted the prognostic value of GATA6 IHC, linking lower GATA6 histoscores to unfavorable survival outcomes in both resected 14 , 17 and advanced PDAC, 18 it is crucial for prospective studies to substantiate these observations. This study, conducted within the confines of an RCT and a rigorously defined clinical framework, adds an extra layer of validation, emphasizing the imperative for continued exploration of GATA6 as a clinically relevant marker.…”
Section: Discussionmentioning
confidence: 99%
“…IHC offers an appealing alternative due to its cost effectiveness, widespread availability, and potential for seamless integration into routine clinical practice. Retrospective studies have already demonstrated strong associations between GATA6 high histoscores and prolonged survival in treatment-naive patients with resected PDAC 14 , 17 and those with advanced disease. 18 However, these studies underscore the necessity of prospective investigations to validate their findings.…”
Section: Introductionmentioning
confidence: 99%